2021
DOI: 10.1136/medethics-2020-106715
|View full text |Cite
|
Sign up to set email alerts
|

‘Who is going to put their life on the line for a dollar? That’s crazy’: community perspectives of financial compensation in clinical research

Abstract: BackgroundFinancial compensation of research participants has been standard practice for centuries, however, there is an ongoing debate among researchers and ethicists regarding the ethical nature of this practice. While these debates develop ethical arguments and theories, they fail to incorporate input from those most affected by financial compensation: potential research participants.MethodsTo identify attitudes surrounding clinical research, participants of a long-standing cohort completed a one-time inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Thus, while payment may be presented as a tool to boost study recruitment efforts [3] or reimburse for time and burdens, it may be implicitly interpreted by potential HIV research participants as a means of compensating for the riskiness of the procedures involved in the research study. This finding complements previous research that has found study payment signals risk level for adults in the general population [5] and that study participants expect to be compensated for physical risks incurred [17].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Thus, while payment may be presented as a tool to boost study recruitment efforts [3] or reimburse for time and burdens, it may be implicitly interpreted by potential HIV research participants as a means of compensating for the riskiness of the procedures involved in the research study. This finding complements previous research that has found study payment signals risk level for adults in the general population [5] and that study participants expect to be compensated for physical risks incurred [17].…”
Section: Discussionsupporting
confidence: 88%
“…Previous research, including of women recruited via MTurk, has shown that women are, in general, more altruistic than men [ 20 , 32 , 33 ]; our finding may extend that altruism to HIV research study participation without payment. Our interpretation of lower levels of interest in HIV research participation without pay among some minoritized racial and ethnic groups and persons with less formal education is that the lack of payment acts as a disincentive to participation, perhaps due to the study risks, a lack of trust in research, or because these groups are more likely to experience income insecurity and may lack the time to participate in activities that do not provide payment as compensation [ 17 , 34 ]. This corroborates our corollary finding that participants identified compensation for time as the most important form of payment for determining research participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A rudimentary coding guide was then developed and revised as data were collected [ 11 ]. The coding guide for themes included a definition, usage instructions, and examples of use [ 13 ]. After each pair coded five transcripts, the pairs were rearranged to prevent coding drift.…”
Section: Methodsmentioning
confidence: 99%
“…Even though Jordan is a developing country (https://datahelpdesk.worldbank.org/ knowledgebase/articles/906519-world-bank-country-and-lending-groups) with a high unemployment rate (https://www.worldbank.org/en/country/jordan/overview), financial incentive was not among the top four motivators and was the least cited barrier for CR participation. Although monetary compensation [52] and self-benefits [49] have been reported in the literature as major facilitators to CR participation, our findings are more in agreement with those from high-income countries in the region such as Saudi Arabia, UAE, and Qatar [20,21,24]. One may argue that this sense of altruism in the Jordanian population has its moral roots, theological origin, or both, and manifested in welcoming a large number of refugees from conflict areas and may provide a sense of usefulness and satisfaction to the participants [11,53].…”
Section: Plos Onementioning
confidence: 99%